Health System Using Social Network to detect the Dengue infection in the specific region - Singh, Vijay; Pant, Bhasker; Singh, Pratap (Indian Journal of Community Health, 2016)
Background: There is law in some countries that each and every health-related event should be recorded or documented digitally and centrally. Unfortunately, this practice is not implemented due to various reasons, that is why the real ground realities differ from what agencies says. Social Network is one of the fastest and effective ways to propagate information without any discrimination and condition. Aims & Objective: By using this beauty of the social network, we proposed a Health System using twitter to detect dengue infected people in the specific region so the concerned agencies take appropriate action proactively and can avoid the epidemic like condition. Material & Methods: Using Naïve Bayes classifier we classify incoming tweets into two categories weather it is promotional tweet or it tells about a dengue infected patient. The method and the proposed health system presented in this article can be applied to another similar task, like to detect communicable disease patients in the specified location. Results: The proposed system is capable enough to give the feel of dengue in the particular region. The results show that the developed system’s efficiency is 57% when testing performs on three set of collected tweets. Conclusion: Twitter can be effectively to get the health status of the society and warned the concerned agencies before the emergency like situation.